Eye, Matter and Interpretation - Larsen, Bente (The Nordic Journal of Aesthetics, 2014)
The main thesis behind the article is that Ad Reinhardt in his Abstract Paintings, through a ‘painting away’ of what traditionally constitutes painting, color, pictorial space and gesture, leads our attention towards visuality. The thesis shall be pursued through a discussion of two different approaches to visual sensing as aesthetic experience, one that prefaces a hermeneutical/phenomenological approach claiming sensuousness to unfold through the gesture of chiasm and ‘intertwining’, as it is formulated by Gottfried Boehm, and another, through Jean-Luc Nancy’s post-phenomenological approach accentuating aesthetic experience as a gesture of distance. In the essay I shall focus on differences between the two and look into the question of how an implementation of a phenomenological chiasm and a hermeneutical claim for meaning in contrast to an epistemological and ontological focus on absence and the picture as Le distinc, leads to fundamental difference concerning the question of meaning, of interpretation.